TRANSMISI HUKUM EKONOMI SYARIAH DI RUANG DIGITAL (KAJIAN TERHADAP AKUN INSTAGRAM @MUAMALAH_DAILY) - Riska Fauziah Hayati (Institut Agama Islam Negeri Batusangkar, 2021)
Nowadays, users of mobile devices are experiencing in increase. Likewise in accessing various social media, one of which is Instagram. Instagram provides various features to disseminate information that supports the fulfillment of people’s information needs. Like the instagram account @muamalah_daily as a medium for transmission muamalah. This paper intends to explore what kind of Islamic economic law discourse is represented by the Instagram account @muamalah_daily, as well as how the discourse is constructed. To answer these questions, the approach used in this study was content analysis. This paper found that Islamic economic law represented in the @muamalah_daily account is dominated by contextual contemporary muamalah fiqh while still paying attention to the basic concepts of classical fiqh. The discourse is constructed in light language that easily understood by the public, and is packaged in an attractive appearance. The @muamalah_daily account is also flexible and systematic in responding to contemporary practices. Along with the times, the practice of sharia economic law is increasingly diverse; many people are still taboo about the law. In this condition, society needs legal knowledge about contemporary economic practices that are still new. Thus, the @muamalah_daily account indirectly influences the Islamic economic law discourse that develops in society.